William MacIntosh, Natural History and the Professionalization of the New Brunswick Museum, 1898-1940 - McTavish, Lianne; Dickison, Joshua (Acadiensis, 2007)
Abstract This article explores the life history of William MacIntosh, the longtime curator of the Museum of the Natural History Society of New Brunswick and the first director of the New Brunswick Museum – both founded in Saint John. His active career as an entomologist and museum worker sheds light on the development of museums within New Brunswick as well as the changes wrought by the gradual professionalization of museum staff during the first half of the 20th century. MacIntosh’s work expands our knowledge of both the cultural history of the Atlantic region and the history of Canadian museums.